Development of a distributed international patient data registry for hairy cell leukemia. Issue 13 (10th November 2022) - Andritsos, Leslie A.; Anghelina, Mirela; Neal, Jasmine; Blachly, James S.; Mathur, Puneet; Lele, Omkar; Dearden, Claire; Iyengar, Sunil; Cross, Matthew; Zent, Clive S.; Rogers, Kerry A.; Epperla, Narendranath; et al.
Abstract: Hairy cell leukemia (HCL) is a rare lymphoproliferative disorder, comprising only 2% of all leukemias. The Hairy Cell Leukemia Foundation (HCLF) has developed a patient data registry to enable investigators to better study the clinical features, treatment outcomes, and complications of patients with HCL. This system utilizes a centralized registry architecture. Patients are enrolled at HCL Centers of Excellence (COE) or via a web-based portal. All data are de-identified, which reduces regulatory burden and increases opportunities for data access and re-use. To date, 579 patients have been enrolled in the registry. Efforts are underway to engage additional COE's to expand access to patients across the globe. This international PDR will enable researchers to study outcomes in HCL in ways not previously possible due to the rarity of the disease and will serve as a platform for future prospective research.